Phytoestrogens Therapy for Osteoporosis Treatment Using Indonesian Medicinal Plants: A Brief Review - Sianipar, Rut Novalia Rahmawati; Iswantini, Dyah; Charlena, Charlena; Wahyudi, Setyanto Tri; Prasetyo, Joni (Science and Technology Indonesia, 2024)
A problematic bone remodeling cycle is known to produce more osteoclasts than osteoblasts, making bones more fragile and this condition shows osteoporosis. In this context, estrogen deficiency in the human body is associated with the regulation of osteoporosis. Therefore, this study aimed to investigate the knowledge about basic concepts of bone, osteoporosis, phytoestrogens, and Indonesian medicinal plants for osteoporosis treatment. Data were obtained from literature on various databases including Science Direct, Wiley Online Library, Scopus, Pubmed, and Google Scholar. Adequate therapy is needed to increase estrogen content and an effective approach is to consume medicinal plants that contain phytoestrogens, which have identical structure and activity to human estrogen (17β-estradiol). The results showed that there were observations comprising in vitro, in vivo, and in silico studies on 18 Indonesian medicinal plants as antiosteoporosis treatments. The Leguminosae or Fabaceae family, which has a significant amount of isoflavones (the primary group of phytoestrogens) was found to dominate as an antiosteoporosis agent. Therefore, the development of phytoestrogens therapy from Indonesian medicinal plants must be implemented for the future treatment of osteoporosis.